Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the given system of linear equations:
[tex]\[ \begin{cases} 6x - 54y = -42 \\ -8x - 3y = 56 \\ \end{cases} \][/tex]
we will follow a detailed, step-by-step approach.
### Step 1: Simplify the Equations (if possible)
First, let's see if the coefficients can be simplified to make the equations easier to work with.
For the first equation:
[tex]\[ 6x - 54y = -42 \][/tex]
Divide every term by 6:
[tex]\[ x - 9y = -7 \][/tex]
So, the first equation simplifies to:
[tex]\[ x - 9y = -7 \quad \text{(Equation 1)} \][/tex]
For the second equation:
[tex]\[ -8x - 3y = 56 \][/tex]
This equation does not simplify any further. Thus, we have:
[tex]\[ \begin{cases} x - 9y = -7 \\ -8x - 3y = 56 \\ \end{cases} \][/tex]
### Step 2: Solve One Equation for One Variable
From Equation 1:
[tex]\[ x - 9y = -7 \][/tex]
Solve for [tex]\( x \)[/tex]:
[tex]\[ x = 9y - 7 \quad \text{(Equation 3)} \][/tex]
### Step 3: Substitute the Expression from Step 2 into the Other Equation
Now substitute Equation 3 into the second original equation:
[tex]\[ -8x - 3y = 56 \][/tex]
Substituting [tex]\( x = 9y - 7 \)[/tex]:
[tex]\[ -8(9y - 7) - 3y = 56 \][/tex]
Simplify and solve for [tex]\( y \)[/tex]:
[tex]\[ -72y + 56 - 3y = 56 \][/tex]
Combine like terms:
[tex]\[ -75y + 56 = 56 \][/tex]
Subtract 56 from both sides:
[tex]\[ -75y = 0 \][/tex]
Solve for [tex]\( y \)[/tex]:
[tex]\[ y = 0 \][/tex]
### Step 4: Substitute Back to Find the Other Variable
Substitute [tex]\( y = 0 \)[/tex] back into Equation 3:
[tex]\[ x = 9(0) - 7 \][/tex]
Simplify:
[tex]\[ x = -7 \][/tex]
### Conclusion
The solution to the system of equations is:
[tex]\[ (x, y) = (-7, 0) \][/tex]
[tex]\[ \begin{cases} 6x - 54y = -42 \\ -8x - 3y = 56 \\ \end{cases} \][/tex]
we will follow a detailed, step-by-step approach.
### Step 1: Simplify the Equations (if possible)
First, let's see if the coefficients can be simplified to make the equations easier to work with.
For the first equation:
[tex]\[ 6x - 54y = -42 \][/tex]
Divide every term by 6:
[tex]\[ x - 9y = -7 \][/tex]
So, the first equation simplifies to:
[tex]\[ x - 9y = -7 \quad \text{(Equation 1)} \][/tex]
For the second equation:
[tex]\[ -8x - 3y = 56 \][/tex]
This equation does not simplify any further. Thus, we have:
[tex]\[ \begin{cases} x - 9y = -7 \\ -8x - 3y = 56 \\ \end{cases} \][/tex]
### Step 2: Solve One Equation for One Variable
From Equation 1:
[tex]\[ x - 9y = -7 \][/tex]
Solve for [tex]\( x \)[/tex]:
[tex]\[ x = 9y - 7 \quad \text{(Equation 3)} \][/tex]
### Step 3: Substitute the Expression from Step 2 into the Other Equation
Now substitute Equation 3 into the second original equation:
[tex]\[ -8x - 3y = 56 \][/tex]
Substituting [tex]\( x = 9y - 7 \)[/tex]:
[tex]\[ -8(9y - 7) - 3y = 56 \][/tex]
Simplify and solve for [tex]\( y \)[/tex]:
[tex]\[ -72y + 56 - 3y = 56 \][/tex]
Combine like terms:
[tex]\[ -75y + 56 = 56 \][/tex]
Subtract 56 from both sides:
[tex]\[ -75y = 0 \][/tex]
Solve for [tex]\( y \)[/tex]:
[tex]\[ y = 0 \][/tex]
### Step 4: Substitute Back to Find the Other Variable
Substitute [tex]\( y = 0 \)[/tex] back into Equation 3:
[tex]\[ x = 9(0) - 7 \][/tex]
Simplify:
[tex]\[ x = -7 \][/tex]
### Conclusion
The solution to the system of equations is:
[tex]\[ (x, y) = (-7, 0) \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.